Henri Cartier-Bresson : the early work - Galassi, Peter (Museum of Modern Art, 1987)
Henri Cartier-Bresson is one of this century's leading photographers. His earliest images are of Europe in the 1930s and '40s. Here is a magnificent compilation of the world-renowned photographer's work that truly captures his famous "decisive moments" through people and places rich in beauty as well as turmoil.